Lipid Profile Changes During the Development of Artemia franciscana, From Cysts to the First Two Naupliar Stages - Lopalco, Patrizia; Lobasso, Simona; Lopes-dos-Santos, Ruy Miguel Alfama; Van Stappen, Gilbert; Corcelli, Angela (Frontiers in Physiology, 2019)
The brine shrimp Artemia is an interesting experimental system for studies of developmental processes. Hatching of dormant cysts gives rise to shrimp larvae called nauplii, characterized by numerous naupliar stages representing the first forms of brine shrimp life cycle. Here combined Thin Layer Chromatography (TLC) and Matrix Assisted Laser Desorption Ionization-Time of Flight Mass Spectrometry (MALDI-TOF/MS) analyses have been performed to gain information on the lipid profiles of cysts and two naupliar stages. Lipid bands isolated after preparative TLC of the lipid extracts have been analysed to detect various species of each lipid class; in addition Post-Source Decay (PSD) analyses allowed the identification of phospholipid chains. We compared the relative abundance of various polar and neutral lipid species in the lipid extracts, proving for the first time that during the development of nauplii there is an increase of cardiolipin (CL) and lysophospholipid levels; in parallel, the amount of phosphatidylcholine (PC) decreases. In addition, as regards neutral lipids, we found an increase of diacylglycerols (DAGs) in correspondence of the decrease of triacylglycerols (TAGs). Data reflect the fact that naupliar stages, being an active form of life, are more metabolically active and offer a platform to develop further studies on the importance of lipid metabolic pathways and bioactive lipids during the development.